2020
DOI: 10.2147/ijn.s242908
|View full text |Cite
|
Sign up to set email alerts
|

<p>Exosome Derived from Coronary Serum of Patients with Myocardial Infarction Promotes Angiogenesis Through the miRNA-143/IGF-IR Pathway</p>

Abstract: Purpose: Myocardial ischemia-reperfusion injury primarily causes myocardial infarction (MI), which is manifested by cell death. Angiogenesis is essential for repair and regeneration in cardiac tissue after MI. In this study, we aimed to investigate the effect of exosomes derived from the serum of MI patients in angiogenesis and its related mechanism. Patients and Methods: Exosomes, isolated from serum, were collected from MI (MIexosome) and control (Con-exosome) patients. After coculturing with human umbilical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 52 publications
0
47
0
1
Order By: Relevance
“…Further, Peng et al (2020) showed that miR-25-3p secreted by MSCs reduces myocardial infarction area by targeting EZH2; Wen et al (2020) showed that exosomal miR-144 derived from MSCs targets the regulation of the PTEN/AKT pathway, thus improving the apoptosis of cardiomyocytes under hypoxia. Geng et al (2020) showed that miR-143, which is derived from serum exosomes, promotes myocardial angiogenesis through the IGF-IR/NO pathway. Collectively, based on the above, exosomal miRNA is expected to become a new method for the diagnosis and treatment of ACS.…”
Section: Cardiovascular Diseases and Exosomal Mirnasmentioning
confidence: 99%
“…Further, Peng et al (2020) showed that miR-25-3p secreted by MSCs reduces myocardial infarction area by targeting EZH2; Wen et al (2020) showed that exosomal miR-144 derived from MSCs targets the regulation of the PTEN/AKT pathway, thus improving the apoptosis of cardiomyocytes under hypoxia. Geng et al (2020) showed that miR-143, which is derived from serum exosomes, promotes myocardial angiogenesis through the IGF-IR/NO pathway. Collectively, based on the above, exosomal miRNA is expected to become a new method for the diagnosis and treatment of ACS.…”
Section: Cardiovascular Diseases and Exosomal Mirnasmentioning
confidence: 99%
“…18 Plasma-derived exosomes are released by a wide range of different cells and that can be internalized by nearby or distant cells, thereby altering their functionality, 19 delivering contents such as cholesterol, proteins, and nucleic acids. 20 As they can protect the encapsulated molecules from external factors, Exos are ideal nanovesicles for use when delivering miRNAs and other bioactive materials to target cells in an effort to modulate gene expression. 21 Fibroblasts are able to readily internalize serum-derived Exos 22 and are essential mediators of wound healing owing to their ability to promote collagen synthesis and localized remodeling of diverse tissue types.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been found that exosomes were widely participating in the physiological and pathological processes of the cardiovascular system, and play an important role in the evolution of heart diseases (21). Furthermore, it was found that exosomes Serum exosome miR-143 was under-expressed in patients with myocardial ischemia-reperfusion injury, and the overexpression of miR-143 inhibited angiogenesis (26).…”
Section: Discussionmentioning
confidence: 99%